P593 Impact of immunomodulating treatment modalities, active smoking and (repeated) COVID19 vaccination on S-antibody seroconversion in IMID patients. Results of the BELCOMID study: BELgian Cohort study of COVID-19 in Immune Mediated Inflammatory Diseases (IMID). (30th January 2023) - Geldof, J; Truyens, M; Sabino, J; Ferrante, M; Lambert, J; Lapeere, H; Hillary, T; Van Laethem, A; de Vlam, K; Verschueren, P; Padalko, E; Lobaton, T; et al.
Abstract: Background: Targeted Immune-Modulating Therapies (TIMT) and immunomodulators (IMM) for Immune Mediated Inflammatory diseases (IMID) theoretically interfere with humoral responses against COVID19. However, IMID patients and particularly patients receiving immunosuppressive treatment were excluded from phase-3 COVID19 vaccination efficacy trials. Real-world observational data is therefore required to provide more insight into the efficacy of COVID19 vaccination in IMID patients. Methods: The BELCOMID study is a multidisciplinary, prospective observational cohort study performed at two university hospitals and set up with the intention to explore the interaction between IMIDs, immune-modulating treatment modalities and SARS-CoV-2 infection and vaccination in a real-life patient cohort. Consecutive patients seen between 17/12/2020 and 28/02/2021 during routine follow-up for IMIDs of the gut, joints and skin were invited to participate. Both patient data and serological samples were collected at 3 predefined periods (Figure 1: before vaccination, after start of the national vaccination campaign before booster vaccination, after booster vaccination). Spike (S) protein antibodies were analysed with the Abbott Architect TM assay. R version 4.0.2 was used to perform analyses. Results: At inclusion period 2, 2065 patients (Table 1) participated of whom 1547 had received complete baseline vaccination (2 doses mRNA-1273, BNT162b2, ChadOx1 nCoV-19 or 1 dose JN78436735). S-antibody seroconversion rate was 91.2%. At inclusion period 3, data was available for 1566 patients of whom 74.7% had received 1 booster (BNT162b2 or mRNA-1273) vaccination leading to a S-antibody seroconversion rate of 98.3%. In 130 patients who had received 2 boosters, S-antibody seroconversion rate was 100%. At period 3, 37 patients had refused all vaccinations. Although 23 of these had experienced confirmed COVID19 since previous inquiry, no S-antibody seroconversion was found in 15 of them. Logistic regression analyses revealed that the odds of no S-antibody seroconversion were significantly higher in IMID patients treated with IMM, combination of IMM+TIMT, systemic steroids and smoking patients at both inclusion periods (Table 2). TIMT monotherapy did not influence seroconversion rates at inclusion period 3 but was associated with higher odds of the lowest S-antibody titre quartile (OR2.32, P<0.001). Among TIMT options, rituximab had higher odds of S-seronegativity. Conclusion: S-antibody seroconversion rate in this real-life IMID population was high after baseline vaccination and increased further proportionally with booster vaccination, highlighting the value of repeated vaccination. However, the serologic response may be blunted due to different IMID treatment modalities and smoking.